Transient Occlusion of Bilateral Internal Iliac Arteries Facilitates Bloodless Operative Field in Subcapsular Prostatectomy - Takumi Takeuchi; Masayoshi Zaitsu; Koji Mikami; Shunsuke Yui; Yuta Takeshima; Naohiko Okamoto; Sadao Imao (Case Reports in Medicine)
Transurethral resection of the prostate is the gold standard of surgical treatment for benign prostatic hyperplasia (BPH). Nevertheless, open subcapsular prostatectomy is still performed for large BPH. While enucleation of prostatic adenoma is being performed, unneglectable bleeding can occur and surgeons need to rush to remove adenomas, often using fingers and in a blinded fashion. The blood supply to the prostatic capsule and adenoma can be reduced to a marked extent in subcapsular prostatectomy if the bilateral internal iliac arteries are transiently occluded. Thus, a bloodless operative field is reasonably acquired during enucleation of adenoma, which would, otherwise, be a cause for concern to surgeons due to bleeding. It is not always applicable, but it could be an option if the estimated volume of BPH is more than 100 mL. In two cases, bilateral internal iliac arteries were occluded with Bulldog clamps, and then adenomas of 159 and 97 g were enucleated.